Determinan Audit judgment Auditor Pemerintah pada Audit Laporan Keuangan Pemerintah Daerah: Studi pada Badan Pemeriksaan Keuangan Perwakilan Provinsi Jawa Tengah dan Badan Pemeriksaan Keuangan Perwakilan Provinsi Daerah Istimewa Yogyakarta - Ilham Maulana Saud; Edwin Heriyanto; Rudy Suryanto (Jurnal Dinamika Akuntansi dan Bisnis, 2018)
This study aims to gain empirical evidence on the influence of knowledge, experience, task complexity, obedience pressure, and professionalism for audit judgment performed by auditor. The samples of this study are auditors who worked at Badan Pemeriksa Keuangan/BPK (or Financial Supervisory Body), representative of Central Java Province and BPK Representative of Yogyakarta Province. The sample selection was conducted by using purposive sampling method. The data collection method was performed by using questionnaire distributed directly to the auditors. There were 140 questionaries distributed but only 76 questionnaires can be processed. Data analysis used a multiple linear regression method. The result of this study shows that knowledge, experience, and professionalism of the auditors have a positive significant effect on thet audit judgment of the auditors, whereas obedience pressure have a significant negative influence for the audit judgment of the auditors. Only the task complexity has not significant effect on the audit judgment taken by auditors.